PENATALAKSANAAN PADA NY. I USIA 54 TAHUN DENGAN DIABETES MELITUS TIPE 2 DAN DISLIPIDEMIA MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS GEDONG TATAAN - Utami, Nabila Rachmadita; Aliffia Bingga, Isvi; Saftarina, Fitria; Putri, Giska Tri (Medula, 2025)
Diseases in Indonesia can generally be divided into communicable diseases and non-communicable diseases. Based on Riskesdas data, the number of DM suffers in Indonesia is increasing every year. In Indonesia, the prevalence of dislipidemia increase to 15.5% in the 55-64 year age group. Of these, 80% of patients died suddenly due to a heart attack, and 20% showed no symptoms. Patients must know about their disease and have awareness and motivation to make lifestyle modifications so that treatment goals can be achieved, so management is needed through a family approach. Application of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on the patient's problem-solving framework with a patient centered approach and a family approach. This study is a case report. Primary data were obtained through anamnesis, physical examination and home visits to assess the physical environment. Secondary data were obtained from patient medical records. Assessments are based on a holistic diagnosis from the start, process, and end of the study in a qualitative and quantitative manner. Mrs. I, 54 years old with type 2 diabetes mellitus (DM) and dyslipidemia, was worried that his complaints would get worse and not improve. Limited knowledge about the patient's health condition in the form of causative factors, prevention of type 2 DM and dyslipidemia, foods that need to be avoided and the lack of motivation and encouragement from families to bring patients for routine health control are factors that cause problems that occur in patients and families. Holistic and comprehensive management of the problems patient named as Mrs. I  has been carried out by providing counseling to increase the knowledge of patients and their families.